Engineering decisions for manufacturing systems : selected, peer reviewed papers from the 2013 2nd International Symposium on Manufacturing Systems Engineering (ISMSE 2013), July 27-29, 2013, Singapore - Jun, Zhang; Tan, Honghua (Applied mechanics and materials ;, 2013)
Collection of selected, peer reviewed papers from the 2013 2nd International Symposium on Manufacturing Systems Engineering (ISMSE2013), July 27-29, 2013, Singapore. The 140 paper are grouped as follows: Chapter 1: Applied Materials Engineering and Materials Processing; Chapter 2: Design and Engineering Researches in Mechanical Engineering; Chapter 3: Environmental Engineering and Energy Sources Engineering; Chapter 4: Opto- and Microelectronics; Chapter 5: Measurements, Detection, Signal and Data Processing; Chapter 6: Mechatronics, Control and Automation of Manufacture; Chapter 7: Information Technology in Manufacturing Systems; Chapter 8: Organization of Manufacture and Engineering Management.